2020
DOI: 10.1111/jan.14504
|View full text |Cite
|
Sign up to set email alerts
|

Mapping publication status and exploring hotspots in a research field: Rheumatoid arthritis with depression

Abstract: Rheumatoid Arthritis (RA) is a systemic autoimmune disease characterized by the chronic erosive arthritis, which causes a high disability rate (Zhou et al., 2013). The global incidence of RA is 0.5-1% (Smolen, Aletaha, & MeInnes, 2016). The aetiology and pathogenesis of this long-term progressive disease are complex, which may be related to both immune factors and the abnormality of synovial cells. RA is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Thus, it could be concluded that Western European countries were the most active regions for the ORA-related research. Although the previous bibliometric studies about RA did not compare the number of documents from the three regions, similar findings have been reported by a bibliometric study on postmenopausal osteoporosis, which found that the number of papers published by Western European authors was about 75% greater than North America authors (24)(25)(26). In specific, as displayed in Table 1, the USA has published the most publications in this domain, with 213 (19.7%) documents, followed by Japan and China, and the remaining countries have published <100 articles.…”
Section: Analysis Of Most Productive Countriessupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, it could be concluded that Western European countries were the most active regions for the ORA-related research. Although the previous bibliometric studies about RA did not compare the number of documents from the three regions, similar findings have been reported by a bibliometric study on postmenopausal osteoporosis, which found that the number of papers published by Western European authors was about 75% greater than North America authors (24)(25)(26). In specific, as displayed in Table 1, the USA has published the most publications in this domain, with 213 (19.7%) documents, followed by Japan and China, and the remaining countries have published <100 articles.…”
Section: Analysis Of Most Productive Countriessupporting
confidence: 76%
“…And their analysis has revealed the most prolific authors, institutions, and journals dealing with the topic. Wang et al conducted a bibliometric study based on the WoS database to explore the publication status and research hotspots in the field of RA-related depression ( 25 ). Additionally, several scholars also investigated the publications on osteoporosis by using bibliometric methods and mapped the overall knowledge structures of the field ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, depression-related bibliometrics research has been gradually carried out. Wang X. et al ( 2020 ) used bibliometrics to analyze the data of annual published papers, major research institutions, core authors and research topics, and then identified the core authors and core teams, analyzed the current research direction of RA-related depression, and predicted new research topics. Hammarström et al ( 2009 ) employed bibiometrics to explain the scientific quality of explanatory biological models associated with gender-related depression.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Several articles on bibliometric analysis of RA have been reported. A bibliometric analysis of the field of RA-related depression was conducted by Wang et al 7 Zhang et al reported a bibliometric analysis of the RA-related interstitial lung disease. 8 However, the bibliometric analysis of research hotspots and keywords related to RA is largely unknown.…”
Section: Introductionmentioning
confidence: 99%